1999
DOI: 10.1016/s0002-9440(10)65286-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Angiogenesis Induces Chromaffin Differentiation and Apoptosis in Neuroblastoma

Abstract: Angiogenesis is a prerequisite for the growth and metastasis of tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 32 publications
2
43
0
Order By: Relevance
“…Three angiostatic agents have been tested recently: the synthetic analogue of fumagillin TNP-470, 39,40 the endogenous steroid 2-methoxyestradiol and its derivative 2-propylestradiol. 41,42 In the TNP-470-treated animals, not only was a significant reduced tumor growth rate observed, but also a reduced microvascular density and a reduction of the fraction of viable tumor cells. 39,40 Furthermore, Wassberg et al 42 demonstrated that the angiogenesis inhibitor TNP-470 induces chromaffin differentiation and apoptosis in NB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three angiostatic agents have been tested recently: the synthetic analogue of fumagillin TNP-470, 39,40 the endogenous steroid 2-methoxyestradiol and its derivative 2-propylestradiol. 41,42 In the TNP-470-treated animals, not only was a significant reduced tumor growth rate observed, but also a reduced microvascular density and a reduction of the fraction of viable tumor cells. 39,40 Furthermore, Wassberg et al 42 demonstrated that the angiogenesis inhibitor TNP-470 induces chromaffin differentiation and apoptosis in NB.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 In the TNP-470-treated animals, not only was a significant reduced tumor growth rate observed, but also a reduced microvascular density and a reduction of the fraction of viable tumor cells. 39,40 Furthermore, Wassberg et al 42 demonstrated that the angiogenesis inhibitor TNP-470 induces chromaffin differentiation and apoptosis in NB. These findings are in agreement with previous observations that apoptotic areas can be considered good prognostic markers in NB.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced antitumour effect of chemotherapeutic agents when combined with AAT (Teicher et al, 1992(Teicher et al, , 1994Sweeney et al, 2001) is probably not only due to differences in vascularisation, perfusion and drug delivery, but also an increase in tumour cell apoptosis (Kamiya et al, 1999;Wassberg et al, 1999). VEGF is a recognised chemoprotectant, particularly for drugs that inhibit microtubules, by reducing the proapoptotic effect of chemotherapy (Tran et al, 2002).…”
Section: Tumour Growth Delaymentioning
confidence: 99%
“…The incidence is 10.5 per million children under 15 years of age per year, with little variation between Europe and North America, and there are 700 new cases diagnosed in the United States each year (Stiller and Parkin 1992;Brodeur 2003). NBs grow rapidly; often giving rise to metastasis (Wassberg et al 1999). Therapy resistance to anticancer drugs represents the major limitation to the effectiveness of clinical treatment.…”
Section: Introductionmentioning
confidence: 99%